Emosional Freedom Tehnique untuk Kesehatan Mental - Angga Dipa Nagara; E Widianti; N Hidayati; Kurniawan Kurniawan (Jurnal Medika Cendikia, 2021)
Overcoming mental problems that are effectively applied to patients with mental disorders is the Spiritual Emotional Freedom Technique (SEFT). Research by Rochjani, Mardiyono, and Arwani (2014) revealed that SEFT therapy can reduce negative emotions in patients with schizophrenia. SEFT therapy with a spiritual approach is suitable to be applied to schizophrenic patients, according to the results that spiritual therapy by doing dhikr, istigfar, and prayer can relieve angry emotions and reduce symptoms that appear in schizophrenic patients. The purpose of writing this article is to see the effectiveness of EFT carried out in psychosis and psychosocial cases. The literature review was compiled by searching for articles on the topic of SEFT for Mental Health in undergraduate and pubmed databases. Keywords include: Emotional Freedom Techniques, Spiritual Emotional Freedom Techniques Mental Health. The inclusion criteria of the selected articles were complete articles of various texts, in the period 2010-2020, articles having DOI, quantitative and qualitative research, using and discussing articles on the application of EFT for various mental health problems both at and psychosocial. The selection article stages use the Preferred Reporting Items for Literature Review and Meta-Analysis (PRISMA) guide which includes 5 steps, namely determining criteria, determining sources of information, selecting literature, collecting data and selecting data items. The article search results obtained 201 articles from scholars and pubmed, according to keywords and based on 2010-2020. After reading the title and abstract, 25 articles met the inclusion criteria and 195 did not. Furthermore, the article is read in full text and there are only 4 articles that can be accessed in full text. The final articles to be analyzed in this literature review are 4 articles. Conclusion: EFT is effective for overcoming mental health problems, both psychosis and psychosocial.